POSSIBILITIES OF DEVELOPMENT OF TOURISM IN SURKHANDARYA REGION - Eralov Azamat Jomurodovich; Ergasheva Yulduz Alimovna (Scholar Express Journal, 2022)
In this article we will talk about the prospects of the visit tourism in the Surkhandarya region. The researcher based on archival data as well as written sources and made clarifications to the problem based on existing scientific and historical literature. He made a comparative analysis of existing approaches and theories on the prospects of development of tourism in the Surkhandarya region
Keywords: Visiting tourism; infrastructure; pilgrimage; tourism